Analisis Teks Mantra Kelahiran Bayi di Desa Cibeureum - Gunawan, Rizal; firdaus, Asep; Ahmad Supendi, Deden (Universitas Islam Sumatera Utara, 2024)
Oral literature as a culture has grown and cultivated in a society that supports it from generation to generation. Mantras are essentially used as a medium to ask God for prayers. Mantras are used as a link between humans and God in the hope that all requests will be granted quickly. This study focuses on structural analysis of the Tali Ari Ari Mantra by analyzing the building blocks, narrative context, and function of both the Tali Ari Ari Mantra. The method used in this research is descriptive qualitative method. The approach used is a qualitative research approach with a descriptive analysis research design. This data collection is done by way of interviews, recording, and recording. The results of this study are in the form of the structure of the Tali Ari Ari spells including the spell building elements for each spell. There are six building elements for the Tali Ari Ari spells resulting in the title element, opening, intention, suggestion element, goal element, element closing. The discussion of the research resulted in two narrative contexts, two functions of the Tali Ari Ari mantra. The context of the narrative on the Tali Ari Ari mantra is the process of the baby giving birth and then the function of the Tali Ari Ari mantra is to expedite when the process of giving birth to a baby goes smoothly without any obstacles